Natural Polyphenols as Inhibitors for the Binding of Covid-19 S-RBD with ACE-2 - Hanai, Toshihiko (Journal of Human Health Research, 2024)
The binding strength of Covid-19 variants, Omicron BQ.1, XBB.1.5, XBB 1.16, FE.1, EG.5, BA.2.86, HV.1, and JN.1, with the ACE-2, was calculated insilicoand evaluated with previous variants; the binding strength of new variants is XBB.1.5 << BA.2.86 < Delta < JN.1 < HV.1 < BA.1 << BA.2. The binding strength of Omicron JN.1 was similar to that of Delta, and that of others was less than that of BA.2.86. The binding inhibition of natural polyphenols was analyzed using a popular Omicron JN.1. The natural polyphenols were (-) Catechin, (+) Catechin, (+) epicatechin, apigenin, apigetrin, daidzein, quercetin, genistein, and oleuropein. The ionization of phenolic hydroxy groups was defined based on the atomic partial charge of oxygen. Polyphenols’ ionized hydroxy groups inhibited the binding of JN.1 S-RPB with ACE-2.
Keywords: SAES-CoV-19 variants; Omicron JN.1; ACE-2; Binding affinity; Binding inhibitor; natural polyphenols